EFFECTS OF PERIODONTAL THERAPY ON CLINICAL PARAMETERS IN PATIENTS WITH RENAL DISORDERS - Earar Kamel; Mioara Decusară; Gabriel-Valeriu Popa; Edlibi al Hage Walid; Dorina-Cerasella Şincar (Romanian Society of Oral Rehabilitation, 2018)
Introduction. Chronic renal disease (BRC) is considered worldwide as a public health problem, mainly due to high morbidity and mortality. Chronic periodontitis (PC) is an immune-inflammatory disease caused by Gram-negative bacteria that destroy tooth support tissues and which induce local inflammation associated with an inflammatory systemic response. Recent studies have shown an association between high levels of reactive protein C PCR) and interleukin-6 (IL-6) and periodontitis, an association that decreases after periodontal treatment (periodontal therapy). Because of this association with the systemic inflammatory response, PC has recently been included as a risk factor for BRC. The purpose of the study. In this study we wanted to evaluate the clinical effect of periodontal treatment in patients with CKD and CP. Materials and methods. The patients were divided into two groups: the first group consisted of CKD patients who were conservatively treated with periodontal treatment and the second group was a control group consisting of patients without any systemic disease who presented moderate to severe CP, also undergoing conservative periodontal treatment. Results. At baseline, PC was more severe in BRC group than in the control group, as most of the sites with the periodontal pocket depth PPD ≥ 5mm periodontal (p = 0.03) and loss of attachment CAL (p = 0.003). However, the results of periodontal treatment were noticeably improved only in the group of patients with periodontal disease but without chronic conditions. Conclusions. Successful periodontal disease reduces the abnormal level of clinical parameters and that can induce an increase of systemic inflammatory response, indicating that it can be animportant intervention therapy at patients with chronic kidney disease.